In vitro bactericidal activities of two novel dihydropyridine derivatives against Mycobacterium tuberculosis - Zandhaghighi, Mehdi; Hadizadeh, Farzin; Soleimanpour, Saman; Meshkat, Zahra; Rezaee, Seyed Abdolrahim; Derakhshan, Mohammad; Ghazvini, Kiarash (The Journal of Infection in Developing Countries, 2017)
Introduction: Introducing new and effective antitubercular agents is important in tuberculosis control programs. In this study, the in vitro antitubercular activity of two novel 1,4-dihydropyridine derivatives (F-27, Cl-33) were screened against a total of 113 different strains of Mycobacterium tuberculosis (77 susceptible and 36 resistant clinical isolates). Methodology: The in vitro activities of these compounds were evaluated based on the modified broth macro-dilution assay. Results: Compound F-27 showed more than 90% growth inhibition at the range of 2 to 8 μg/mL (minimum inhibitory concentration [MIC]90: 4.13 ± 0.45 µg/mL; p < 0.01), and complete growth inhibition was observed at the range of 8 to 32 μg/mL (minimum bactericidal concentration [MBC]: 11.2 ± 1.65 µg/mL; p < 0.01) against susceptible strains. However, 92% of the resistant strains showed some degree of susceptibility against this compound (MIC90 range: 16 to 64 µg/mL; mean: 40.4 ± 8 µg/mL; p < 0.01). It was found that although there is a linear relationship between the inhibitory activity of F-27 and isoniazid against resistant strains at low concentrations (r = 0.484, p < 0.001), there was no relationship between resistance to isoniazid and F-27 at higher concentrations (r = 0.019, p > 0.1). This may emphasize no cross-resistance between F-27 and isoniazid. Conclusions: Considering the sufficient sample size of the study and based on the excellent antimycobacterial activity of F-27, it could be concluded that F-27 is a potent candidate as a lead compound, and may be considered for development of a new antitubercular agent.